Challenges in Sustaining Employees in Call Centers, Hyderabad - Gollapalli, Sai Sarvani (2008)
The purpose of this work is to investigate the challenges faced by human resource managers in Hyderabad call centres in sustaining their employee pool‟s. Business Process Outsourcing organizations face the highest attrition rates in the world. This research not only plays a crucial exploratory to discover the causes of attrition and the strategies required to reverse the current situation but also addresses the core factors inhibiting the industry to overcome losses worth millions of dollars. The work follows a case study approach in which data is collected through existing literature and semi structured interviews which are then analysed using popular qualitative methods to produce key findings. The findings show labour shortages coupled with the need of business expansion as one of the most substantial faced in call centers in Hyderabad.